Peran Pengadilan Dalam Pemberian Perlindungan Hukum Terhadap Anak Sebagai Korban Kekerasan Seksual - Purba, Paska Riando; Debora, Debora (CV. Rayyan Dwi Bharata, 2025)
Legal protection for child victims of sexual violence aims to realize children's human rights. Crimes of decency or moral offences and sexual harassment are two forms of violation of decency which are not only a matter of national law of a country but are legal problems of all countries in the world or a global problem. Sexual abuse of children requires special attention considering the consequences of sexual violence against children which results in prolonged trauma to children. Children who are afraid to tell the events they experience, have a great opportunity for the perpetrator to carry out the next action. The formulation of the problem in this study is how the role of the court in providing legal protection to children as victims of sexual violence, how the obstacles faced by the Tarutung District Court in providing protection to children as victims of sexual violence. This research uses a sociological juridical method, namely research on problems by looking at and paying attention to the applicable legal norms linked to the facts that exist from the problems encountered in the research. The legal protection provided by the court is medical rehabilitation which is a process of integrated treatment activities by restoring the physical condition of children, child victims and / or child witnesses.